TRENDS IN THE DEVELOPMENT OF EDUCATION AND UPBRINGING OF ORPHAN CHILDREN IN CHILDREN’S HOUSES OF THE CHINESE PEOPLE’S REPUBLIC (Comparative Professional Pedagogy, 2021)
The article analyzes the trends in the development of education and upbringing of orphans in orphanages in modern China. Leading researchers have identified orphanages as the main form of social care for orphans and their education and upbringing in China. Most orphanages in cities have several departments: an orphanage (for children from 0.3 to 3 years old), an orphanage (children from 3 to 14 years old), a department for the disabled and a nursing home. China's education system consists of compulsory preschool education, primary education, incomplete and complete secondary school, higher education, and higher education. All levels of the education system for orphans are free in China. Orphans also have the right to receive the level of education they need for their age. China’s 9-Year Compulsory Education Act was passed in 2004. The organization of educational and upbringing processes in educational institutions for orphans is in accordance with the norms and programs developed by the relevant Ministry and departments for secondary schools. The article proves that the main focus in the country is on education, not training, as the priority is still to master the vast majority of the population in working professions. The purpose of the article is to theoretically analyze the trends in the development of education and upbringing of orphans in orphanages of the People’s Republic of China. As a result of the analysis of works of foreign and domestic scientists we can state that the main trends in the maintenance, education and upbringing of orphans in modern China are adaptation to the social structure of China, state control of educational institutions, age-appropriate orphans in orphanages, creating conditions for the education of orphans according to age, promoting ideological, moral, patriotic, economic education.
Keywords: orphans; education; upbringing (moral, labor, patriotic, aesthetic); orphanages; compulsory preschool education; primary education; incomplete and complete secondary school